Factors Associated With Early and Late Post-stroke Fatigue in Patients With Mild Impairment. Results From the Stroke Cohort Study Augsburg - Kirchberger, Inge; Wallner, Florian; Linseisen, Jakob; Zickler, Philipp; Ertl, Michael; Naumann, Markus; Meisinger, Christine (Frontiers in Neurology, 2022)
Background Post-stroke fatigue (PSF) is a common symptom after stroke. However, studies on the factors associated with early and late PSF are scarce. The objective of this study was to identify variables associated with early and late PSF. Methods In the German Stroke Cohort Augsburg (SCHANA) study, patients were interviewed during their hospital stay and completed a postal questionnaire 3 and 12 months post stroke. PSF was assessed using the Fatigue Assessement Scale (FAS). In addition, depressiveness were measured by the Patient Health Questionnaire (PHQ-9), general health status by the EQ-5D visual analogue scale, and physical activity by the the International Physical Activity Questionnaire (IPAQ). Multivariable regression models were used to determine the associations between FAS scores at 3 and 12 months post stroke and demographic, psychosocial and health-related covariables. Results Among 505 patients, the frequency of PSF was 31.1% 3 months and 29.1% 12 months post stroke. Prior stroke (ß=2.37, p=0.0076), prior diagnosis of depression (ß=5.04, p=0.0001), higher NIHSS (ß=0.25, p=0.0360) and PHQ-9 scores (ß=0.55, p<0.0001) were significantly related with higher fatigue levels 3 months post stroke. Additionally, younger age (ß=-0.07, p=0.0219), a worse rating of general health at baseline (ß=-0.04, p=0.0287) and low pre-stroke physical activity (ß=-0.0004, p=0.0089) were significantly associated with higher fatigue levels 12 months after stroke. Conclusions PSF is a common and persisting syndrome even in patients with mild impairment. Prior depressive disorder and early depressive symptoms were the most relevant predictors of both early and late fatigue.